Evaluating the risk and risk factors of dysautonomia as a post-acute sequelae of COVID-19: a secondary analysis of a matched case–control dataset - Pierson, Benjamin C.; Craig-Kuhn, Megan Clare; Stewart, Laveta; Sercy, Erica; Stern, Caryn A.; Graham, Brock; Michel, Amber; Parmelee, Edward; Koehlmoos, Tracey Perez; Saunders, David; Mancuso, James D.; Pollett, Simon; et al. (Frontiers in Neurology, 2025)
BackgroundA significant proportion of patients presenting with post-acute sequelae of COVID-19 (PASC) have been found to meet diagnostic criteria for certain disorders of the autonomic nervous system. Substantial gaps remain in our understanding of these conditions. Our objective is to evaluate demographic and medical factors associated with PASC dysautonomia in active duty US Service members (ADSM). Additionally we assessed for risk factors in those diagnosed with COVID-19 for PASC dysautonomia, and differences in those with PASC dysautonomia and non-PASC dysautonomia.MethodsA matched case control dataset (n = 1,367,961) of ADSM diagnosed with COVID-19 matched with ADSM with no evidence of COVID-19 was utilized to assess associations of demographic and clinical factors with PASC dysautonomia. Logistic regression modeling was used to assess differences among those diagnosed with COVID-19. Conditional logistic regression modeling using propensity score weighting was used for comparisons between those with PASC dysautonomia and non-PASC dysautonomia.ResultsWe identified 619,983 COVID-19 cases (158 PASC dysautonomia) and 747,978 controls (219 non-PASC dysautonomia). Among COVID-19 cases, factors positively associated with PASC dysautonomia were white, non-Hispanic race/ethnicity, female sex, younger age, northeast region, more severe COVID-19 infection, and comorbid depression or anxiety. Among those with dysautonomia, those with PASC dysautonomia were more likely to be of female sex, younger, in the northeast region, and less likely to have comorbid anxiety.ConclusionPASC dysautonomia is rare in ADSM but associated with increased care utility and often prolonged diagnostic pathways. Important demographic and COVID-19 specific risk factors are associated with the development of PASC dysautonomia. PASC dysautonomia has significant differences in risk factors as compared to non-PASC dysautonomia, warranting further examination. These findings may support clinician awareness and prognostication and prompt further research on the pathophysiology and management of these conditions.